City Rehabilitation with Community Participation on Cultural and Social Rejuvenation - Suwannarat, Samart (Journal of International Buddhist Studies, 2015)
This paper purposes to archive for translation of how Chiang Mai communities with in an urban aspect seeking methods to success their aims on community rehabilitation through heritage conservation. Overall representation comes from a development project by non-governmental alliance, named Fuen Baan YaanWieng Project which recruited varied partners from scholars, youth professionals and governor officers. The project focuses on promote the unique value of Chiang Mai old city and the community participation to conserve its heritage. The methodology of this project applied three steps of rehabilitation process 1) Identification of community’s unique value 2) a procedure on cultural and social rejuvenation based on community participation 3) How a center place or social system assemble a support for the program. The three steps are manifested as a core value to reveal questions and move forwards to implement and reach out community and alliance understanding. The result shows through the pilot projects based on community participation and community opinion which all excellent represent a good path way of community and city rehabilitation. Additionally, community has learned and experienced to rejuvenate their old social and cultural ecology; which gradually collapsed by urbanization. The communities have applied cultural and heritage assets as a tool along with collaboration and empowerment from varied agents who focused on cultural and heritage conservation as well. The new model of working with participatory approach has become a core concept which presently widespread over the old city and gradually started its impact in city level.